Glucagon like peptide-2 and neoplasia; a systematic review. (4th March 2018) - Ring, Linea Landgrebe; Nerup, Nikolaj; Jeppesen, Palle Bekker; Svendsen, Lars Bo; Achiam, Michael Patrick
ABSTRACT: Introduction : Glucagon like peptide-2 is synthesized from enteroendocrine L cells primarily located in the ileum and large intestine. GLP-2 stimulates crypt cell proliferation, increases intestinal blood flow, enhances gut barrier function, induces mucosal healing, and exerts an anti-apoptotic effect. Due to these effects GLP-2 is used in the treatment of short bowel syndrome (SBS). Areas covered: The aim of this systematic review was to provide information on the potential risk of intestinal neoplasia in patients receiving treatment with GLP-2. The literature search was performed independently by two authors in the following databases; Pubmed, Embase, Scopus, Web of Science and Cochrane. Expert commentary: This systematic review indicated that treatment with GLP-2(1–33) up to 30 months in humans without any known pre-existing cancer did not confer an increased risk of intestinal neoplasia in patients or animals. However, due to the small amount of patients studied it is premature to reach any final conclusions about GLP-2 – induced neoplasia. GLP-2(1–33) treatment in animals with a pre-induced cancer showed that GLP-2(1–33) may promote growth of existing neoplasia.